Pricing Synthetic CDOs Using a Three Regime Random-Factor-Loading Model - Philip Messow (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Synthetic Collateralized Debt Obligations (CDOs) were among the driving forces of the rapid growth of the market for credit derivatives in recent years. Possibly the most popular model beside the Gaussian copula for pricing CDO tranches is the Random-Factor-Loading-Model of Andersen and Sidenius (2005). We extend this model by allowing more than two regimes of default correlations. The model is calibrated to market spreads at times of financial distress and during calm periods. For both points in time the model correlation skews are similar to the steep skews observed in the market and lead to an improvement to the standard Random-Factor-Loading-Model. – – Einer der maßgeblichen Faktoren für das rasante Wachstum des Kreditderivatemarktes der letzten Jahre sind synthetische Collateralized Debt Obligations (CDO). Zur Bepreisung von CDOs werden in der Praxis vor allem die Gauss'sche Copula als auch das bekannte 'Random-Factor-Loading'-Modell von Andersen und Sidenius (2005) benutzt. Im Rahmen dieser Arbeit wird dieses Modell von zwei auf drei mögliche Korrelationsregime erweitert und empirisch überprüft. Hierfür werden sowohl Marktdaten aus ruhigen und turbulenten Phasen an den Finanzmärkten verwendet. Für beide Zeitpunkte sind die Modellspreads ähnlich wie die am Markt beobachtbaren Spreads.
Keywords: C58; G13; 330; Collateralized debt obligation; random-factor-loading; pricing; financial dependence; factor model; default risk; correlated defaults